The preparation of calcium phosphate coatings on titanium and nickel-titanium by rf-magnetron-sputtered deposition: Composition, structure and micromechanical properties; Surface and Coatings Technology; Vol. 202, iss. 16 - Pichugin V. F. Vladimir Fyodorovich; Surmenev R. A. Roman Anatolievich; Shesterikov E. V. Evgeny Viktorovich; Ryabtseva M. A.; Eshenko E. V.; Tverdokhlebov S. I. Sergei Ivanovich; Prymak O.; Epple M. (2008, 2008)
Title screen